2019
DOI: 10.1080/13621718.2019.1629379
|View full text |Cite
|
Sign up to set email alerts
|

Wire and arc additive manufactured Ti–6Al–4V/Al–6.25Cu dissimilar alloys by CMT-welding: effect of deposition order on reaction layer

Abstract: Components of Ti-6Al-4 V/Al-6.25Cu dissimilar alloys were manufactured via wire and arc additive manufacturing (WAAM) using cold metal transfer (CMT) technology. Additive manufactured components were obtained irrespective of the deposition order. When the Ti alloy was deposited first, brazing joining occurred between the Ti and Al alloys and TiAl 3 formed in the reaction layer. Otherwise, fusion joining occurred, and TiAl 3 , TiAl, and Ti 3 Al formed in a thicker reaction layer. The average tensile strengths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…TA1 to IN625 (Lu et al , 2021) functionally graded thin-walled structure was developed using a dual wire WAAM process and NiTi 2 , NiTi, TiNi 3 and Laves phases were reported in the structure with increased hardness due to the presence of Cr and Mo enriched phases. Tian et al (2019) deposited Ti-6Al-4V to AlSi 5 FGS through the WAAM process and found that the interface layers consist of continuous layers of intermetallics, Ti 7 Al 5 Si 12 and because of this, the failure occurred at the interface layer. The average tensile strength of the component was approximately 80 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…TA1 to IN625 (Lu et al , 2021) functionally graded thin-walled structure was developed using a dual wire WAAM process and NiTi 2 , NiTi, TiNi 3 and Laves phases were reported in the structure with increased hardness due to the presence of Cr and Mo enriched phases. Tian et al (2019) deposited Ti-6Al-4V to AlSi 5 FGS through the WAAM process and found that the interface layers consist of continuous layers of intermetallics, Ti 7 Al 5 Si 12 and because of this, the failure occurred at the interface layer. The average tensile strength of the component was approximately 80 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…A wire and arc additive manufacturing (WAAM) technology was chosen in welding-brazing of Ti-6Al-4V/Al-6.25Cu dissimilar joint. However, the joint properties were still not satisfying [14]. All the referenced studies above were focused on Ti/Al lap joining; the Ti/Al butt MIG joining has been rarely studied but by the authors.…”
Section: Introductionmentioning
confidence: 99%
“…A few attempts were carried *Corresponding author: tel. : +86 351 3557519; e-mail address: wszweishouzheng@126.com out using MIG welding, and some progress was made [8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%